THE PRESERVATION OF MILK WITH THE ADDITION OF ANTIBACTERIAL AND AROMATIC SUPPLEMENTS PRODUCED IN INDONESIA - Tatik Khusniati; Yantyati Widyastuti (BIOTROPIA, 2008)
The preservation of milk with additional antibacterial and aromatic supplements, produced in Indonesia, was investigated. Organoleptic performances of milk with the addition of 10% supplements, made as juices, were tested by panellists, and the total bacteria, protease activities, lipase activities and acidities, were detected by total plate counts, azocasein method, modified dole extraction and base-acid titration, respectively. Out of the 27 supplemented skim and whole milk samples, 15 whole milk samples and 10 skim milk samples were selected as acceptable, based on their better organoleptic performances, their lower bacterial counts, protease and lipase activiÂties, and their acidities percentages which were not significantly different, compared to that of control, at 5 days after the expiry date (P